Contribution Of Social Media To The Development Of Hospitality Industry – A Case Study Of Barbeque Nation ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2022)
Background: In this era of the internet social media has taken a valuable place in terms of  providing information, connecting, and socializing. The hotel industry of the 21st century has  also accepted this situation and doing everything to connect with their customers through  various platforms. Barbeque nation has been chosen as a brand to study since it is available  at 138 locations in India. Objective: To understand the relationship between social media  marketing traits (entertainment, interaction, customer engagement, and word of mouth), brand attachment, and purchase intention. Methodology: This is a quantitative study, and a  structured questionnaire was given to respondents that were selected through the  convenience sampling method. All the respondents were from Delhi. The analysis of data was  done through IBM SPSS 21 statistics tool. Exploratory factor analysis and regression  analysis has been applied to analyse the data of 245 respondents (63.3% male and 35.9 %  female). Results: The results revealed that the word of mouth is the strongest predictor of  purchase intention followed by the interaction. Entertainment is also found to be a key  variable in attracting customers by Barbeque Nation. Conclusion: On analysis, it was found that all the social media marketing traits and brand attachment somewhere affect the purchase intention. The results of this study can be used by managers to plan strategies for  their future and existing customers.
Keywords: Social Media Marketing Traits; Brand Attachment; Purchase Intention; Customer Engagement; Word of Mouth